2021
DOI: 10.1021/acs.est.1c06460
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Carbon: A Key Fraction Determining the Light Absorption Properties of Methanol-Soluble Brown Carbon of Open Biomass Burning Aerosols

Abstract: The composition and radiative forcing of light-absorbing brown carbon (BrC) aerosol remain poorly understood. Polycyclic aromatics (PAs) are BrC chromophores with fused benzene rings. Understanding the occurrence and significance of PAs in BrC is challenging due to a lack of standards for many PAs. In this study, we quantified polycyclic aromatic carbon (PAC), defined as the carbon of fused benzene rings, based on molecular markers (benzene polycarboxylic acids, BPCAs). Open biomass burning aerosols (OBBAs) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…73,74 Nitrophthalic acid, the hydrolysis product of nitrophthalic anhydrides, was also identified as a chromophore in the aerosols produced by the combustion of biomass. 75 Since both of these hydrolysis products are organic markers of SOA, 76−79 the hydrolysis of anhydrides can be used to track the formation and evolution of secondary BrC. Overall, our findings highlight the influence of NO 3 levels and pre-existing particles on the chemical composition and optical properties of nighttime furan SOA, whereas bulk and molecular characterizations of SOA constituents and chromophores are necessary for better experimental constraint and a more complete process-level understanding of their formation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…73,74 Nitrophthalic acid, the hydrolysis product of nitrophthalic anhydrides, was also identified as a chromophore in the aerosols produced by the combustion of biomass. 75 Since both of these hydrolysis products are organic markers of SOA, 76−79 the hydrolysis of anhydrides can be used to track the formation and evolution of secondary BrC. Overall, our findings highlight the influence of NO 3 levels and pre-existing particles on the chemical composition and optical properties of nighttime furan SOA, whereas bulk and molecular characterizations of SOA constituents and chromophores are necessary for better experimental constraint and a more complete process-level understanding of their formation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Even under wet conditions where anhydrides could be hydrolyzed, the resulting products may still be chromophores. For example, phthalic acid (or 1,2-benzenedicarboxylic acid), the hydrolysis product of phthalic anhydride, has been reported as one of the most prevalent BrC chromophores in ambient observations. , Nitrophthalic acid, the hydrolysis product of nitrophthalic anhydrides, was also identified as a chromophore in the aerosols produced by the combustion of biomass . Since both of these hydrolysis products are organic markers of SOA, the hydrolysis of anhydrides can be used to track the formation and evolution of secondary BrC.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Several studies have revealed that some components of BrC include nitro‐aromatics, polycyclic aromatic hydrocarbon (PAHs), polyphenols, and sulfur‐containing compounds (Bluvshtein et al., 2017; Budisulistiorini et al., 2017; Fleming et al., 2018; R. J. Huang et al., 2018; Lin et al., 2016; Y. Sun et al., 2021; Yuan et al., 2021). Numerous observation and laboratory studies have shown that secondary BrC could be formed from anthropogenic and biogenic precursors via multiphase chemistry under various conditions, and those formation processes have been partially revealed through laboratory simulations (Aiona, Lee, Leslie, et al., 2017; Aiona, Lee, Lin, et al., 2017; Kampf et al., 2016; Lambe et al., 2013; C. Li, He, Fang, et al., 2020; Siemens et al., 2022; Y. Wang, Mekic, et al., 2021; J. Xu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that some components of BrC include nitro-aromatics, polycyclic aromatic hydrocarbon (PAHs), polyphenols, and sulfur-containing compounds (Bluvshtein et al, 2017;Budisulistiorini et al, 2017;Fleming et al, 2018; R. J. Lin et al, 2016;Y. Sun et al, 2021;Yuan et al, 2021).…”
mentioning
confidence: 99%
“…On the other hand, the chemical composition of secondary BrC produced by the Fe-PC reactions is mysterious, making it difficult to evaluate its effect on haze formation as well as its potential health hazards. The application of ultrahigh-resolution Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) provides an opportunity to enhance our understanding of atmospheric OA at the molecular level. It has been used to investigate the molecular diversity of OA fractions collected from various atmospheric samples ,, and to elucidate the relationships between the optical properties of OA and their molecular compositions. , However, no research has tried to reveal the molecular characteristics of phenols derived from secondary BrC using FT-ICR MS, and how different phenolic precursors affect the molecular composition of secondary BrC remains unclear. In addition, no attempt has been made to compare laboratory-generated BrC with real OA at the molecular level.…”
Section: Introductionmentioning
confidence: 99%